Compton scattering from superstrings - Azevedo, Thales; Matamoros, Daniel E. A.; Menezes, Gabriel [UNESP] (Springer Nature, 2025)
We propose a candidate Compton amplitude which is valid for any (integer) quantum spin and free from any spurious poles. We consider the cases of electromagnetism and gravity. We obtain such amplitudes by calculating the corresponding ones from superstring theory involving states on the leading Regge trajectory. To extract the associated field-theory amplitudes a few considerations in the form of simple physical constraints are required, such as: soft momentum transfer, compactification of polarizations and consistent factorization in the physical channels. We believe the present exploration will be significantly relevant for the physics of compact binary systems with spin.
Keywords: Classical Theories of Gravity; Scattering Amplitudes; Superstrings and Heterotic Strings